Al‐Shifa Healthcare Information System in Oman: A Debatable Implementation Success. Issue 1 (5th December 2017) - Al‐Gharbi, Khamis N.; Gattoufi, Said M.; Al‐Badi, Ali H.; Al‐Hashmi, Ali A.
Abstract: This paper presents a case study of the project management of Al‐Shifa healthcare information system (HIS) in Oman. In addition to the reports about the project made available to the researchers, the focus group methodology was used for collecting the relevant information from the main project's stakeholders. The paper describes first the evolution of the implementation of an HIS tailored by the Ministry of Health (MOH) in Oman to fit the needs of the healthcare units under its supervision. The case analysis that constitutes the second element in the paper is made based on the Project Management approach developed by the Project Management Institute (PMI). As a matter of fact, the authors found that there was no formal project management approach adopted by the MOH for the development and implementation of the hereto‐mentioned HIS project. Moreover, the project has experienced a chronic creep in terms of features, cost and time‐schedule. The recommendations of the authors for the rescue of the project from its current dilemma, consist of technological, administrative and human resource development actions.